C677T Gene Polymorphism of MTHFR Is a Risk Factor for Impaired Renal Function in Pregnant Women With Preeclampsia in the Chinese Han Population - Yun, Lin; Ge, Meiqi; Xu, Rui; Zheng, Fei; Zhao, Xueqiang; Li, Xinran (Frontiers in Cardiovascular Medicine, 2022)
Impaired renal function in pregnant women with preeclampsia is particularly common, yet there is no consensus about implementation. This lack of consensus is due in part to uncertainty about risks for disease progression. Limited evidence suggests that C677T gene polymorphism of 5, 10-methylenetetrahydrofolate reductase (MTHFR C677T) may affect impaired renal function in pregnant women with preeclampsia in Chinese Han population. To investigate the association between MTHFR C677T and impaired renal function in pregnant women with preeclampsia, a total of 327 pregnant women diagnosed with gestational hypertension (GH) or preeclampsia-eclampsia (PE) from January 2016 to December 2021 were selected as the study subjects. The personal information, gestational information, clinical indicators, and the C677T gene polymorphism of MTHFR were tested. Compared with the GH group, the PE renal function impairment group had increased in blood pressure, homocysteine level, liver and kidney function indicators (creatinine, uric acid, urea nitrogen, cystatin C, alanine aminotransferase, aspartate aminotransferase, cholyglycine), and blood lipids (total cholesterol, triglycerides and low density lipoprotein) but had reductions in plasma protein (total protein, albumin, globulin, prealbumin), trace elements (calcium and zinc), prothrombin time and fibrinogen. The homocysteine level in the TT genotype was higher than that in the CC and CT genotypes. Binary logistic regression analysis showed that the MTHFR C677T gene polymorphism was associated with PE renal function impairment in the recessive model (OR: 1.620, 95% CI: 1.033–2.541, P < 0.05). These findings show that the C677T gene polymorphism of MTHFR is an independent risk factor for impaired renal function in pregnant Chinese Han women with PE.